Business law : an active learning approach (Oxford : Blackwell, 1996)
The English legal system. Legal relationships. Business contracts. Non-contractual obligations of the seller/producer. European community law.
Keywords: Business; Law; Great Britain; Commercial law; Commercial law -- Great Britain; Commercial law -- European Economic Community countries